2D Redox‐Active Covalent Organic Frameworks for Supercapacitors: Design, Synthesis, and Challenges. Issue 22 (18th January 2021) - Li, Miao; Liu, Jingjuan; Zhang, Ting; Song, Xiaoyu; Chen, Weihua; Chen, Long
Abstract: Due to the tunable skeletons, variable pore environments, and predesignable structures, covalent organic frameworks (COFs) can be served as a versatile platform to tailor redox activities for efficient energy storage. Redox‐active COFs with specific functional groups can not only promote high‐speed mass transport in the permanently open channels, but also provide dense active sites for reversible redox reactions so as to efficiently adsorb the electrolyte ions, thus becoming emerging and promising electroactive materials. This review summarizes the design principles and synthetic methods of redox‐active COFs, with a focus on surveying the representative advances in supercapacitors. The key progress, major challenges, and future directions in this promising field are highlighted as well. Abstract : Redox‐active covalent organic frameworks (COFs) with specific functional groups, ordered structures, and regular open channels are promising electroactive materials for supercapacitors (SCs). This review focuses on surveying the design principles, synthetic methods, and representative advances of redox‐active COFs in SCs. Key challenges and future directions of 2D redox‐active COFs in this field are proposed as well.